2010
DOI: 10.1007/s10591-010-9130-6
|View full text |Cite
|
Sign up to set email alerts
|

Three Authors, One Client: A Qualitative Description of Marriage and Family Therapy Initial Case Documentation

Abstract: During the client screening and initial session process at a marriage and family therapy training clinic, three types of forms are completed: a Telephone Information Form (TIF), completed by an intake coordinator; a Client Information Form (CIF), completed by the client; and a first session Progress Note (PN), completed by the therapist. The researchers examined documents from closed client files of cases seen by masters students at a university-based brief therapy training clinic. Qualitative descriptive anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Intake forms are used to document demographic history and current concerns, and typically include contact information, identifying characteristics, relevant background information (e.g., treatment history, previous diagnoses, medical information, family history), payment information, and reasons for seeking treatment (Heller, Gilliam, Chenail, & Hall, 2010). This information permits providers to confirm diagnoses and determine if services are within their scope of specialization.…”
Section: Record Keeping Documentsmentioning
confidence: 99%
“…Intake forms are used to document demographic history and current concerns, and typically include contact information, identifying characteristics, relevant background information (e.g., treatment history, previous diagnoses, medical information, family history), payment information, and reasons for seeking treatment (Heller, Gilliam, Chenail, & Hall, 2010). This information permits providers to confirm diagnoses and determine if services are within their scope of specialization.…”
Section: Record Keeping Documentsmentioning
confidence: 99%
“…Retrospective studies have examined consistency in agency documentation. For example, Heller, Gilliam, Chenail, and Hall (2010) examined closed records of a universitybased brief therapy clinic to assess the level of consistency in documentation forms completed by the client, the intake coordinator, and the master's-level counseling student. That study utilized a small sample of 20 closed records and found high levels of consistency in the recording among all three individuals providing information on presenting problems and other questions on the form.…”
Section: Gaps In the Literature On Documentation Continuing Educationmentioning
confidence: 99%